Discovery of trisubstituted nicotinonitrile derivatives as novel human GCN5 inhibitors through AlphaScreen-based high throughput screening. Issue 9 (8th February 2019) - Tao, Hongru; Wang, Jun; Lu, Wenchao; Zhang, Rukang; Xie, Yiqian; Liu, Yu-Chih; Liu, Rongfeng; Yue, Liyan; Chen, Kaixian; Jiang, Hualiang; Zhang, Yuanyuan; Xu, Xiaohui; et al.
Abstract : The trisubstituted nicotinonitrile derivative DC_HG24-01 was discovered as a novel potent hGCN5 inhibitor with efficient bioactivity against MV4-11 cells. Abstract : The general control nonrepressed protein 5 (GCN5) is an important target for drug design and drug discovery largely owing to its pathogenic role in malignancies. Chemical probes that target GCN5 have been developed in recent decades, but their potencies are still unsatisfactory. In this study, through an in-house developed AlphaScreen-based high throughput screening platform, radioactive acetylation assays and 2D-similarity based analogue searching, we discovered DC_HG24-01 as the novel hGCN5 inhibitor with the IC50 value of 3.1 ± 0.2 μM. Further docking studies suggested that DC_HG24-01 could occupy the binding pocket of acetyl-CoA cofactor, which laid the foundation for the development of more potent hGCN5 inhibitors in the future. At the cellular level, DC_HG24-01 could retard cell proliferation and block the acetylation of H3K14 leading to cell apoptosis and cell cycle arrest at the G1 phase in MV4-11 cell lines. Taken together, the discovery of DC_HG24-01 may serve as a good starting point to accelerate the development of more potent hGCN5 inhibitors through further structural decoration and provide new insight into the pharmacological treatment of leukemia.